Online learning communities and teacher professional development [ methods for improved education delivery - Lindberg, J. Ola , 1966-; Olofsson, Anders D. , 1973- (Information Science Reference, 2010)
"This book features innovative applications for the integration of technology into everyday teaching practices"--Provided by publisher.